Possibilities and limits of Joyce Travelbee's theory for the construction of a family care methodology - Maria Angélica Pagliarini Waidman; Ingrid Elsen; Sonia Silva Marcon (Universidade Federal de Goias, 2006)
This is a theoretical, reflexive study that has as its aim to present Joyce Travelbee's theory and to analyze its limitations and potentialities, with the purpose of building a family care methodology. To do so, I made an explanation of the theory including the author's concepts, beliefs and principles. I have also performed a review of several authors that used this theories in their scientific studies and I finally present a reflection begining with the theory analysis, its expliciting its possibilities and its limits and how it can be used as a base for the development of a care methodology for families that have members with mental disorders, aiming at taking these people from the mental institutions and reinserting them in their families and community.